Espíritu festivo : cuentos de fantasmas - Davies, Robertson, 1913-1995 (Libros del Asteroide, 2013)
Presents an entertaining and witty collection of eighteen stories about ghosts and other haunting tales of the supernatural, including such notable literary apparitions as Ibsen and Charles Dickens.